Effect of confined and unconfined stress on jointed rocks - Singh T.N.; Singh V.K. (My University, 2025)
The behaviour of rockmass depends on the loading behaviour and their surroundings. The Chunar sandstone of Vindhyan System has been tested in confined and unconfined stress conditions with different joint orientations 30°, 45°, 60° and 90°. It is found that uniaxial compressive strength increases as the value of joint orientation increases. It has also been observed that strength of specimens having joint orientation 90° is highest under the same confinement. As the confinement increases the strength increases at the same angle of joint orientation.